Gestão em redes para a construção de políticas públicas: um estudo sobre as atividades e prevenção e repressão à lavagem de dinheiro no Brasil - Augustinis, Viviane Franco de (2011)
This study aimed to investigate and compreehend how the emergence of network public management styles can contribute to construct public policies that attend public interest. The theoretical framework was based on interorganizational network theories and, more specifically, on public policy network theories. The main focus of the research was therefore to study relations of collaboration and cooperation that transcend organizacional boundaries and provide more flexibility and greater scope to the process of constructing public policies. The empirical context chosen for discussion was the relationship between brazilian institutions that work together in anti-money laundering efforts. This context has been chosen by the perception that the practice of financial crimes bring huge losses to countries that need to overcome economic and social inequalities. The construction of public policies that are relevant and effective in the prevention and punishment of money laundering crimes can be translated into benefits for the entire economy of a nation. The reflexive methodology proved to be the most suitable for achieving the goals of this research. From the construction of empirical data, it was possible to create constructs that sintetize benefits and challanges of public policy networks. The following interpretative conections reinforce the idea that the external network performance will be perceived by society as more effective the better the internal network performance. If internal network performance improves, it becomes possible to overcome endogeous and exogenous barriers to the network, what improves the results of interaction among participants, leading to more effective results for society.